2020
DOI: 10.1088/2053-1591/ab735b
|View full text |Cite
|
Sign up to set email alerts
|

Sr addition and its effect on the melt cleanliness of A356

Abstract: Strontium modification of Al-Si alloys has known to have several beneficial effects such as increased feedability, the formation of fibrous Si and increased mechanical properties. However, in the presence of Sr, during melting and holding durations, the oxide structure of the dross may change which leads to several problems during casting operations. In this work, the amount of Sr was changed and the melt was held for 1 h. Reduced Pressure Test (RPT) was used to asses melt quality change and it was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, the porosity formed due to the precipitation of the dissolved gas during the solidification process is generally spherical. However, there are reports on theories specifically on complex connections between bifilms and gas porosities [36,37].…”
Section: Reduced Pressure Testingmentioning
confidence: 99%
“…On the other hand, the porosity formed due to the precipitation of the dissolved gas during the solidification process is generally spherical. However, there are reports on theories specifically on complex connections between bifilms and gas porosities [36,37].…”
Section: Reduced Pressure Testingmentioning
confidence: 99%
“…Oxide Films and Dispersoids. Atakav et al [39] investigated the effect of Sr addition on the melt cleanliness of A356 alloy. Reduced pressure test (RPT) was used to assess melt quality change and it was found that cleanliness was increased due to the fading of Sr.…”
Section: 3mentioning
confidence: 99%
“…Al‐7Si‐based alloys are widely used for industrial applications, and A356 aluminum alloy is a representative of such alloys as an indispensable material in automotive parts [1]. Particularly, the alloy needs further studies to improve its properties.…”
Section: Introductionmentioning
confidence: 99%